Social Parenthood in Comparative Perspective - Huntington, Clare; Joslin, Courtney G. 1971-; Bary, Christiane von 1988- (New York University Press, 2023)
Investigates social parents - people who function as parents but who may not be recognized as such in the eyes of the law What makes a person a parent? Around the world, same-sex couples are raising children; parents are separating and re-partnering, creating blended families; and children are living with grandparents, family friends, and other caregivers. In these situations, there is often an adult who acts like a parent but who is unconnected to the child through biogenetics, marriage, or adoption-the common paths for establishing legal parenthood. In many countries, this person is called a "social parent." Psychologically, and especially from a child's point of view, a social parent is a parent. But the legal status of a social parent is hotly debated. Social Parenthood in Comparative Perspective considers how the law does-and how it should-recognize social parenthood.